Most wanted - Hogan, David Glenn; Wayans, Keenen Ivory; Voight, Jon, 1938-; Hennessy, Jill, 1968-; New Line Cinema Corporation; New Line Home Entertainment (Firm) ([United States?] : New Line Home Entertainment, 2001)
Wrongly imprisoned, Marine Sgt. James Dunn is offered a chance to join an ultra-covert operations unit headed by Colonel Grant Casey. But when his first mission goes awry, Dunn is targeted as the fall guy. As the massive manhunt closes in on him, he must now employ all his lethal military skills to expose the truth and face the perpetrators.
Container title: From most honored to most wanted.
Originally released as motion picture in 1997.
For specific features see interactive menu.
Executive producers, Tony Mark, Keenen Ivory Wayans ; producer, Eric L. Gold ; original music, Paul Buckmaster ; cinematography, Marc Reshovsky.
Keenen Ivory Wayans, Jon Voight, Jill Hennessy, Paul Sorvino, Robert Culp, Wolfgang Bodison, Simon Baker Denny, Eric Roberts.
Rated R.
Keywords: Marines -- Drama; Action and adventure films; DVDs for the hearing impaired; Feature films